Revocable policy-based chameleon hash using lattices - Klamti Jean Belo; Hasan Mohammed Anwarul (Journal of Mathematical Cryptology)
A chameleon hash function is a type of hash function that involves a trapdoor to help find collisions, i.e., it allows the rewriting of a message without modifying the hash. For some applications, it is important to have the feature of revoking the rewriting privilege of the trapdoor holder. In this paper, using lattice-based hard problems that are considered quantum-safe, we first introduce a lattice-based chameleon hash with an ephemeral trapdoor (CHET)\left({\mathsf{CHET}}) and then a revocable attribute-based encryption (RABE{\mathsf{RABE}}) scheme that is adaptively indistinguishable. We also give security analyses of our schemes and compare our RABE{\mathsf{RABE}} scheme to two relevant schemes proposed recently. Furthermore, we combine our CHET{\mathsf{CHET}} and RABE{\mathsf{RABE}} to design a new revocable policy-based chameleon hash.